Detection and delineation of oral cancer with a PARP1 targeted optical imaging agent - Kossatz, Susanne (Sci Rep, 2016)
Earlier and more accurate detection of oral squamous cell carcinoma (OSCC) is essential to improve the prognosis of patients and to reduce the morbidity of surgical therapy. Here, we demonstrate that the nuclear enzyme Poly(ADP-ribose)Polymerase 1 (PARP1) is a promising target for optical imaging of OSCC with the fluorescent dye PARPi-FL. In patient-derived OSCC specimens, PARP1 expression was increased 7.8 ± 2.6-fold when compared to normal tissue. Intravenous injection of PARPi-FL allowed for high contrast in vivo imaging of human OSCC models in mice with a surgical fluorescence stereoscope and high-resolution imaging systems. The emitted signal was specific for PARP1 expression and, most importantly, PARPi-FL can be used as a topical imaging agent, spatially resolving the orthotopic tongue tumors in vivo. Collectively, our results suggest that PARP1 imaging with PARPi-FL can enhance the detection of oral cancer, serve as a screening tool and help to guide surgical resections.